The products of the gradients of perpendicular lines is "-1." That is to say, "mm' = -1"
Let's assume that the gradient of the line perpendicular to the line "y = \\dfrac {1} {2} x + 4" is "m."
"=> m(\\dfrac {1}{2}) = -1"
"=> \\dfrac {1}{2}m = -1"
"=> m = -2"
Point-slope form
"ANSWER: \\space y + 2 = -2(x - 3)"
"SOLUTION"
The general point-slope form of a linear equation is
"y - y_{1} = m(x - x_{1})" where "m" is the slope/gradient and "(x_{1}; y_{1})" is the point.
In this case, "m = -2 \\space and \\space points \\space x_{1} = 3 \\space \\& \\space y_{1} = -2 \\space from \\space the \\space point \\space (3; -2)"
"\\therefore \\space y - (-2) = -2(x-3)"
"=> y + 2 = -2 (x - 3)"
Slope-intercept form
"ANSWER: y = -2x + 4"
"SOLUTION"
The general slope-intercept form of a linear equation is given by "y = mx + c" where "m" is the slope/gradient and "c" is the "y-intercept."
Now, "m = -2" , therefore "y = -2x + c"
Substituting the point "(3; -2)" to find "c:" "-2 = -2(3) + c"
"=> -2 = -6 + c"
"=> c = -2 + 6"
"=> c = 4"
"\\therefore \\space y = -2x + 4"
Comments
Leave a comment